Industrialization 2.0 in the Russian Federation: Professional Aspect - P'yankova Lyudmila (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Industrialization 2.0 presupposes reproducing human capital through higher education. By highlighting the problems associated with Industrialization 2.0, the author identified the discussion field around its models, as well as the factor system of the current industrial and technological order. The contemporary technological paradigm integrates cyber-physical systems, robotics, and advanced technologies, e.g., IoT, AI, into the industrial production. The current national technological lag is caused by obsolete capacities, as well as by poor technological, economic, and anthropological adaptation to the new global economy. The growing military industry has been affecting the national economy since 2022. After the collapse of the USSR, the shift to a market economy caused a crisis of industrial production: only new high-tech industries will make it possible to overcome the current dependence on raw materials. The insufficient development of bioinformatics and communication technologies curbs the economic efficiency and national security. The limited access to foreign technologies emphasizes the importance of technological independence, especially in microelectronics. A better competitiveness needs better mechanisms for investment and personnel retraining based on a human-centered model. If resolved, this anthropological dilemma will change the supply and demand on the labor market, increase industrial productivity, and initiate the development of advanced skills.